Age-related changes in calbindin and calretinin immunoreactivity in the central auditory system of the rat - Ouda, Ladislav; Burianova, Jana; Syka, Josef (Experimental gerontology, 2012)
Age-related changes in the levels of major intracellular calcium buffers are known to occur in different parts of the mammalian brain, including the central auditory pathway. In the present study, we evaluate with immunohistochemistry and the western blot technique the effect that aging has on the calbindin- and calretinin-expressing system of neurons in the higher structures of the central auditory pathway, in the inferior colliculus (IC), medial geniculate body (MGB) and auditory cortex (AC) of two rat strains, the slowly aging Long-Evans and the fast aging Fischer 344. Interestingly, the age-related changes demonstrated a similar character regardless of the rat strain. In the IC of young animals, the majority of calbindin and calretinin immuno-reactive (CB and CR-ir) cells were found in the dorsal and external cortices and only sparse positive cells were present in the central nucleus of the IC. With aging, the number of CB-ir and CR-ir neurons decreased significantly in both the dorsal and external cortices. Furthermore, these declines were accompanied by an age-related reduction in the mean volumes of CB- and CR-ir neuronal somas. In the MGB of young rats, CB-ir neurons were present in abundant numbers in both the dorsal and ventral subdivisions, while CR-ir neurons were practically absent in this structure. With aging, the number and mean volume of CB-ir cells in the ventral subdivision of the MGB were significantly decreased. In comparison with the IC and MGB, age-related numerical and volumetric declines of both CB-ir and CR-ir neurons in the AC were less pronounced. Western blot protein analysis revealed a pronounced age-related decline in the levels of calbindin in both strains and in all examined brain regions. In contrast, the decline in calretinin levels with aging was less prominent, with a significant decline only in the IC of both strains. The observed age-related changes in the calbindin- and calretinin-expressing systems may contribute significantly to the deterioration of hearing function known as central presbycusis.
Keywords: potkani inbrední F344; colliculus inferior; Inferior Colliculi; druhová specificita; Aging; Calbindin 2; sluchové korové centrum; Brain; Rats, Long-Evans; kalbindiny; imunohistochemie; neurony; Species Specificity; krysa rodu Rattus; Animals; Auditory Cortex; Immunohistochemistry; zvířata; S100 kalcium vázající protein G; Neurons; Rats; Calbindins; stárnutí; mozek; Rats, Inbred F344; S100 Calcium Binding Protein G; metathalamus; kalbindin 2; potkani Long-Evans; Geniculate Bodies